Creation care : a biblical theology of the natural world - Moo, Douglas J; Moo, Jonathan A. (Jonathan Andrew), 1975- (Biblical theology for life, 2018)
From Genesis to Revelation, the Bible reveals a God whose creative power and loving care embrace all that exists, from earth and sky and sea to every creeping, crawling, swimming, and flying creature. Yet the significance of the Bible's extensive teaching about the natural world is easily overlooked by Christians accustomed to focusing only on what the Bible says about God's interaction with human beings. In Creation Care, part of the Biblical Theology for Life series, father and son team Douglas and Jonathan Moo invite readers to open their Bibles afresh to explore the place of the natural world within God's purposes and to celebrate God's love as displayed in creation and new creation.